A territory scale analysis of habitat preferences of the declining Ortolan Bunting Emberiza hortulana. Issue 1 (2nd January 2016) - Brambilla, Mattia; Gustin, Marco; Vitulano, Severino; Negri, Irene; Celada, Claudio
Abstract : Capsule Ortolan Bunting occurrence is associated with bare ground, Lucerne, shrub cover and hedgerows/tree rows. Aims To assess the habitat features selected by Ortolan Buntings at the territory level in semi-open landscapes, in the northern Apennines of Italy. Methods We mapped territories in ten different plots and built a habitat selection model comparing 52 occupied cells with 52 unoccupied ones (cell size: 1 ha). We built multivariate adaptive regression splines models based on ground-measured variables. Results The model revealed an association with intermediate Lucerne cover (50% of the cell), high shrub cover, bare ground (≥5%) and hedgerows/tree rows (≥25 m/ha). The most important driver of occurrence was bare ground (optimum at 5–20%). Conclusion The maintenance of the mosaic and low-intensity farmed landscape, the promotion of Lucerne and the conservation/restoration of hedgerows/tree rows, may be promoted through the Rural Development Programme. The conservation of bare soil, grassland and shrubs at optimum amount at fine-scale could be the object of an agri-environment scheme targeted specifically at the Ortolan Bunting.